Genetic and pharmacologic suppression of PPARγ enhances NELL-1-stimulated bone regeneration. (August 2022) - Tanjaya, Justine; Ha, Pin; Zhang, Yulong; Wang, Chenchao; Shah, Yash; Berthiaume, Emily; Pan, Hsin Chuan; Shi, Jiayu; Kwak, Jinny; Wu, Benjamin; Ting, Kang; Zhang, Xinli; et al.
Abstract: Recent investigations into mechanisms behind the development of osteoporosis suggest that suppressing PPARγ-mediated adipogenesis can improve bone formation and bone mineral density. In this study, we investigated a co-treatment strategy to enhance bone formation by combining NELL-1, an osteogenic molecule that has been extensively studied for its potential use as a therapeutic for osteoporosis, with two methods of PPARγ suppression. First, we suppressed PPARγ genetically using lentiviral PPARγ-shRNA in immunocompromised mice for a proof of concept. Second, we used a PPARγ antagonist to suppress PPARγ pharmacologically in immunocompetent senile osteopenic mice for clinical transability. We found that the co-treatment strategy significantly increased bone formation, increased the proliferation stage cell population, decreased late apoptosis of primary mouse BMSCs, and increased osteogenic marker mRNA levels in comparison to the single agent treatment groups. The addition of PPARγ suppression to NELL-1 therapy enhanced NELL-1's effects on bone formation by upregulating anabolic processes without altering NELL-1's inhibitory effects on osteoclastic and adipogenic activities. Our findings suggest that combining PPARγ suppression with therapeutic NELL-1 may be a viable method that can be further developed as a novel strategy to reverse bone loss and decrease marrow adiposity in age-related osteoporosis.